(3GdeLed aj GdZdhSjeGWjbG (B: s (3OQGSI aj efgGLjI GdEfSGfjGJ eY EMGdI NGUI Ydi GddSGfjGJ (B: (3GdfXQjI GdYGeI (B/ s - (3ChdOGd, gGfR jhQZfs; (3EScfOQ, jhSas ((3HjQhJ (B:s (3LGeYI GdchaI, s, 2019)
(3GdZdhSjeGWjbG eTQhY HMK GhSY ef GddSGfjGJ hgj JJeGgi eY eG jSejg GhdOGd GdYdhe ZjQ GdcejI GfgG Jbhe Ydi efXhQ NGdU ef GdeHGfj GdTcdjI GdJj JgOa Gdi GSJcfGg GdTehdjI GdJj jbhe YdjgG LhgQ GddZI hGdGfXeI GdeeGKdI ef NdGd JMdjd eSJhjj GddZI, GdJYHjQ hGdeMJhi Gdi GdZdhSjeGJ hgj GUZQ GdechfGJ GdJj jba YfOgG GdJMdjd(B.s
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020.s
(3jTJed Ydi bGFeI eUWdMGJ(B.s
Keywords: (3GddZGJs; (3GddgLGJs